2019
DOI: 10.22571/2526-4338131
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia do canabidiol no tratamento de convulsões e doenças do sistema nervoso central: revisão sistemática

Abstract: As terapias empregadas no tratamento de doenças do sistema nervoso central são complexas e em sua maioria trazem inúmeros efeitos adversos, levando a indústria farmacêutica a pesquisar sobre novas substâncias e produzir medicamentos mais eficazes e menos agressivos ao paciente, com o objetivo de estudar a eficácia do canabidiol no tratamento de convulsões epiléticas e demais doenças do sistema nervoso central. O método adotado foi uma pesquisa exploratória qualitativa, realizada através de busca ativa nas base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
21

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 10 publications
0
5
0
21
Order By: Relevance
“…[174] The authors reported as hort and divergent synthesis of diastereoisomer (+ +)-34 through stereospecific 1,3metal migration of iodine olivetol derivatives with alkyl derivatives of (S)-perillicacid (56;Scheme 21). [175] For arylation of olefins, the authors synthesized aryl iodide 59 through the iodation of 27 in the presence of KI, m-CPBA, and [18]crown-6 as at ransfer agent,f ollowedb yO -protection of 58 with CH 3 Ia nd K 2 CO 3 ,i n5 8% overall yield after the two steps.S eparately,t he methylation of 58 with LDA followed by the addition of Me 2 Sg ave the terpenic intermediate 59 In an alternative synthetic route, Vaillancourt and Albizati suggested using both the stereoselective substitution of bulky terpenic derivatives-mediated by organometallic speciesand ac hemoselective rearrangement under highly basic conditions as key reactions to form (À)-2 (Scheme 22) and its advancedintermediate( À)-34 (Scheme 23). [124] According to the authors, the chemo-and stereoselective synthesis of (À)-2 (Scheme 22) proceeded throughnucleophilic substitution of 3,9-dibromocamphor intermediate 28 [176,177] with homocuprate 54,w hich was obtained from 21,i n7 1% yield.…”
Section: Aromatic Coupling Mediated By Organometallic Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…[174] The authors reported as hort and divergent synthesis of diastereoisomer (+ +)-34 through stereospecific 1,3metal migration of iodine olivetol derivatives with alkyl derivatives of (S)-perillicacid (56;Scheme 21). [175] For arylation of olefins, the authors synthesized aryl iodide 59 through the iodation of 27 in the presence of KI, m-CPBA, and [18]crown-6 as at ransfer agent,f ollowedb yO -protection of 58 with CH 3 Ia nd K 2 CO 3 ,i n5 8% overall yield after the two steps.S eparately,t he methylation of 58 with LDA followed by the addition of Me 2 Sg ave the terpenic intermediate 59 In an alternative synthetic route, Vaillancourt and Albizati suggested using both the stereoselective substitution of bulky terpenic derivatives-mediated by organometallic speciesand ac hemoselective rearrangement under highly basic conditions as key reactions to form (À)-2 (Scheme 22) and its advancedintermediate( À)-34 (Scheme 23). [124] According to the authors, the chemo-and stereoselective synthesis of (À)-2 (Scheme 22) proceeded throughnucleophilic substitution of 3,9-dibromocamphor intermediate 28 [176,177] with homocuprate 54,w hich was obtained from 21,i n7 1% yield.…”
Section: Aromatic Coupling Mediated By Organometallic Speciesmentioning
confidence: 99%
“…[13][14][15] Research into cannabidiol ((À)-2,C BD)a ddresses its use in severalt herapeutic applications, including as an anticonvulsant. [16][17][18] The first use of a highly purified oral solution of CBD to treat epilepsy-related diseases took place in the USA in 2018. Approvedb yt he FDA, the extract is distributed and marketed under the name of Epidiolex by GW Pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atualmente muitas doenças que são alvos de terapias medicamentosas profundas e resultam em diversos efeitos colaterais ao usuário, isso faz com que as indústrias produtoras de medicamentos vivam em uma constante e interminável busca por novas substâncias e medicamentos que sejam mais efetivos e menos ofensivos no tratamento dessas doenças. Em decorrência disso o pensamento da indústria farmacêutica tem se voltado para os vegetais que possuem efeitos farmacológicos comprovados que antes eram considerados totalmente marginalizados como é o caso do Cannabis sativa (SANTOS, 2019).…”
Section: Eficácia Da Cannabis Sativa No Tratamento De Doençasunclassified
“…A literatura reporta a extração de inúmeros canabinoides a partir da Cannabis sativa. Dentre os quais destaca-se o canabidiol (CBD), cujos efeitos farmacológicos tem sido extensivamente relatados no tratamento de doenças relacionadas ao Sistema Nervoso Central (SNC), como epilepsia e autismo (NOREEN et al, 2018;SCHERF;MENDES, 2019). Apesar disso, a Cannabis sativa e seus produtos são classifi cados pela "Drug Enforcement Administration" como uma substância com alto potencial para abuso.…”
Section: Introductionunclassified